Senegal : Staff Report for the Article IV Consultation and Third Review Under the Policy Support Instrument-Press Release, and Staff Report. - International Monetary Fund. African Department (Washington, D.C. : International Monetary Fund, 2017)
Implementation of the "Plan Senegal Emergent" (PSE) is beginning to pay dividends, contributing to projected growth of over 6 percent for the second year in a row. However, for growth to be sustained, further reforms are needed to improve the business environment and create economic space for private domestic and foreign investment. The challenge of meeting infrastructure development objectives without undermining debt sustainability will require continuing efforts to improve the quality of investment while pursuing a prudent debt strategy that keeps the cost of borrowing at reasonable rates. Failure to strengthen debt management and master treasury operations may jeopardize the rating of low risk of debt distress.
Print version record.
Keywords: Senegal -- Economic conditions; Economic history; Senegal; Electronic books